A Dual-Band Non-destructive Dielectric Measurement Sensor Based on Complementary Split-Ring Resonator - Wang, Chen; Liu, Xiaoming; Gan, Lu; Cai, Qing (Frontiers in Physics, 2021)
A dual-band non-destructive dielectric constant sensor based on the complementary split ring 14 resonators is presented. The resonators for both bands use the complementary split ring structure of 15 different sizes. Numerical simulation demonstrates that the resonating frequency and quality factor is 16 dependent on the variation of dielectric constant and loss tangent, making it a potential structure for 17 dielectric measurement. To search for the optimal thickness for measurement, parametric study is 18 conducted and the retrieval expressions are obtained for both bands. The measured results indicate an 19 accuracy of 1.5% in comparison with the data in the literature. In addition, the effect of air gap has 20 been analyzed, showing that it is an important error source and eliminating such effect can improve 21 the measurement accuracy.